Uncovering visual narratives about human mobility on telegram - Carneiro, Bia; Tucci, Giulia; Ruscica, Giosue (2024)
This poster summarizes the results of the research project conducted during the 2024 Digital Methods Initiative Summer School "Visual methods for digital research". The research project aimed to investigate human mobility visual narratives that emerge from Telegram images' visual vernaculars. After creating curated lists of Telegram groups and channels, the TeleCatch software was employed to construct datasets for six thematic case studies. The application of Artificial Intelligence tools to analyse image collections generated from these datasets uncovered a range of visual narratives depicting human mobility across the case studies.